2019
DOI: 10.5539/gjhs.v11n10p16
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mind Subtraction Meditation on Smartphone Addiction in School Children

Abstract: Background: Aim of current study was to examine the effects of school-based mind subtraction meditation program on smartphone addiction tendency and mental health of third grade students in a South Korean elementary school. Materials and Methods:A quasi-experimental design with nonequivalent comparison groups was used. An experimental group (n = 24), who participated in the school-based meditation program, and a control group (n = 22), who did not participate in the program, were measured pre-test, post-test, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Even after one month of completing the program, the total scores of smartphone addiction tests were decreased in the experimental group. This beneficial effect of the meditation program also was noted in other research studies related to meditation [11,26,27]. A prior study showed that a school-based mind subtraction meditation had a positive effect on smartphone addiction tendency and the addiction-associated mental health of children in South Korea [11].…”
Section: Influence On Smartphone Addition By Mind Subtraction Meditationsupporting
confidence: 71%
See 1 more Smart Citation
“…Even after one month of completing the program, the total scores of smartphone addiction tests were decreased in the experimental group. This beneficial effect of the meditation program also was noted in other research studies related to meditation [11,26,27]. A prior study showed that a school-based mind subtraction meditation had a positive effect on smartphone addiction tendency and the addiction-associated mental health of children in South Korea [11].…”
Section: Influence On Smartphone Addition By Mind Subtraction Meditationsupporting
confidence: 71%
“…There have been numerous studies on finding ways to prevent smartphone addiction [10]. Among those which remain effective, mind subtraction meditation is the one which has been widely applied as a school-based program in South Korea [11].…”
Section: Mind Subtraction Meditationmentioning
confidence: 99%
“…Terefore, this meditation has been called "True Self meditation" or "Mind Subtraction meditation" [11]. Other researchers have utilized this meditation method and reported that it was easily learned and practiced among younger populations, such as school-aged children [27], college students [20], and young adults [28].…”
Section: Ethical Considerations and Datamentioning
confidence: 99%